Transcriptome study on immune response against Vibrio parahaemolyticus challenge in gill of abalone Haliotis discus hannai Ino - Fang, Yan; Yang, Xiyun; Zhang, Shujuan; Chen, Xuyang; Lin, Gang; Zhang, Yuqing; Wang, Mengjiao; Li, Mingzhu (Frontiers in Marine Science, 2022)
Abalone (Haliotis discus hannai Ino) is one of the most vital economic shellfish cultured in China. However, bacterial and viral infection often leads to its high mortality and serious economic losses. In this study, transcriptome sequencing was performed on gill of abalone challenged by Vibrio parahaemolyticus for 0 h (control group, A0h), 8 h (A8h), and 48 h (A48h), respectively. Each library has an average of 53,361,675 clean reads. Approximately 85.71% reads were mapped to the reference genome of Haliotis discus hannai Ino. In comparison with A0h group, 7,656 and 2,789 genes were differentially expressed in the A8h and A48h groups, respectively. The differentially expressed genes (DEGs) were mostly enriched in oxidation–reduction process and oxidoreductase activity from GO analysis as well as immunity and metabolism-related pathways from Kyoto Encyclopedia of Genes and Genomes analysis. Cluster analysis demonstrated that all DEGs were categorized into eight subclusters by adopting the gene expression model. Specifically, a total of 1,070 significantly downregulated genes from two clusters were related to some metabolic pathways, ABC transporters, and cell adhesion. Moreover, 212 upregulated genes in one subcluster were enriched in several immune-related pathways, including nucleotide-binding oligomerization domain (NOD)-like receptor signaling pathway and apoptosis. Some members of the pattern recognition receptors family, which can initiate inflammatory signaling and induce apoptosis, were stimulated to upregulate in gill after challenge including C1q, perlucin, and low-density lipoprotein receptor–related protein. In addition, caspase-dependent apoptosis pathway was inactive, whereas caspase-independent apoptosis pathway was stimulating in response to Vibrio challenge. To eliminate invading pathogen, the immune effectors such as interleukin-17, matrix metalloproteinase, lysozyme, superoxide, and ferritin were also stimulated in gill. Moreover, this study also provides more information for comprehending the immunity and defense mechanisms against V. parahaemolyticus infection in abalone.